2016
DOI: 10.1007/s12020-016-1197-x
|View full text |Cite
|
Sign up to set email alerts
|

Reduced serum levels of oestradiol and brain derived neurotrophic factor in both diabetic women and HFD-feeding female mice

Abstract: The estrogen levels in the pre and post menstrual phases interact with brain-derived neurotrophic factor in a complex manner, which influences the overall state of the body. To study the role of oestradiol and brain-derived neurotrophic factor in modulating obesity related type 2 diabetes and the interactions between two factors, we enrolled 15 diabetic premenopausal women and 15 diabetic postmenopausal women respectively, the same number of healthy pre and postmenopausal women were recruited as two control gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…BDNF is a major member of the neurotrophin (NT) family. Patients suffering acute coronary syndrome (ACS) [ 38 ], acute myocardial infarction (MI) [ 39 ], metabolic syndrome [ 40 ] and type-2 diabetes [ 41 , 42 ] have decreased circulating BDNF levels. Decreased circulating BDNF levels have been associated with endothelial dysfunction [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…BDNF is a major member of the neurotrophin (NT) family. Patients suffering acute coronary syndrome (ACS) [ 38 ], acute myocardial infarction (MI) [ 39 ], metabolic syndrome [ 40 ] and type-2 diabetes [ 41 , 42 ] have decreased circulating BDNF levels. Decreased circulating BDNF levels have been associated with endothelial dysfunction [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study found that high fat diet-fed mice with impaired glucose tolerance expressed lower level of BDNF mRNA in VMH. HFD leads to changes of BDNF in VMH by affecting the central insulin signaling pathway ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…One of the most potent NTs is BDNF. Although the expression of BDNF primarily affects the central nervous system, this unique factor is also present in serum, which has been confirmed in numerous clinical and preclinical studies [29,30,31]. As potential sources of BDNF, blood platelets, brain neurons, and vascular endothelial cells are mentioned [32].…”
Section: Discussionmentioning
confidence: 99%